Periodontal Disease as a Potential Risk Factor for Alzheimer’s Disease - An Evaluative Study - Achari Aiswarya; Suragimath Girish; Varma Siddhartha; Zope Sameer; SR Ashwinirani (Indian Journal of Dental Research)
Context: Alzheimer’s disease (AD) is a cognitive impairment disorder, affecting the routine daily activities. Bidimensional relationship exists between periodontal disease and AD, where periodontal disease could exacerbate the severity of AD and cognitive decline reduces the oral hygiene maintenance, increasing the severity of periodontal disease. Dentists should recognize the relationship between periodontal disease and Alzheimer’s for better patient management. Aims: The study aims to assess the knowledge, awareness, and practices about periodontal disease as a potential risk factor for Alzheimer’s disease among dentists. Settings and Design: This cross-sectional survey consisting of 20 structured, close-ended questionnaire was circulated among dentists practicing in Western Maharashtra, India. Materials and Methods: Google form consisting of pre-validated, structured 20 questionnaire was the means to acquire data from dentists willing to participate in the study. The link to google form questionnaire was mailed to the dentists. Statistical Analysis Used: Chi-square tests were used to determine the association of predictors/risk factors (periodontal disease) with AD. Statistical analysis was performed using Statistical Package for Social Sciences software. Results: 185 dentists participated in the study. The study’s results revealed a significant lack of knowledge and awareness (P < 0.001) among dentists about the correlation between periodontal disease and AD. Conclusions: Dentist’s overall knowledge, awareness, and practices were lacking regarding the association between periodontal disease and AD. Dentists should be educated about the bidirectional relationship between AD and periodontal disease, through continuing dental education programs. The patients and caregivers should be educated about oral hygiene and health maintenance for long-term benefits.